Expression of Leadership Abilities of Students of the Basic Music Education Programme in a Music School: A Case Study - Venslavičienė, Loreta; Venckienė, Diana (Jaunųjų mokslininkų darbai, 2024)
The development of leadership skills is a continuous and ongoing process, starting in childhood. Leadership is associated with personal qualities – creativity, initiative, critical thinking, etc. This is not a natural trait, but something that has to be learnt, and education has an important role to play in the development of young leaders. Music school education focuses on subject achievements that are important for musical activity, on the development of artistic skills, and often overlooks the development of leadership skills that are important for personal maturity. Since it is assumed that the application of the transformational leadership model could enable the development of the expression of leadership skills, the article analyses the prerequisites for the expression of leadership skills in music school educational activities and the possibilities of their improvement in a particular music school in order to achieve the comprehensive success of a person’s (self-)education. The findings of the empirical research suggest that teachers in a music school focus on the development of musical abilities, while the development of leadership skills becomes a self-occurring consequence of the organisation of the process, rather than a well-thought-out and purposefully pursued goal.